Dramatic Increase in the Incidence and Mortality from Merkel Cell Carcinoma in the United States. Issue 8 (August 2015) - Fitzgerald, Timothy L.; Dennis, Samuel; Kachare, Swapnil D.; Vohra, Nasreen A.; Wong, Jan H.; Zervos, Emmanuel E.
Merkel cell carcinoma is a cutaneous neuroendocrine neoplasm that has been poorly studied in contemporary cohorts. Patients with Merkel cell carcinoma from 1986 to 2011 were identified in the Surveillance Epidemiology and End Results registry. A total of 5211 patients met the inclusion criteria. The mean age was 74.9 years; majority were male (61.4%) and white (94.9%). Patients were divided into two cohorts: Group 1 (1986 and 1999) and Group 2 (1999–2010). Group 2 was more likely to have Stage III disease (14.6 vs 23.3%, P < 0.001) and less likely to have Stage I/II disease (71.8 vs 65.1%, P < 0.0001). The increase in Stage III was likely secondary to increased use of sentinel lymph node biopsy. Disease-specific five-year survival for Stages I/II was 78.1 per cent and Stage III was 54 per cent. Disease-specific five-year survival was unchanged between Groups 1 and 2, 69.9 versus 66.6 per cent, respectively ( P = 0.44). Both incidence and mortality significantly increased over the study period with P value for both trends <0.0001. In 1986, incidence and mortality rates per 100, 000 were 0.22 and 0.03, respectively, and increased to 0.79 and 0.43 in 2011, respectively. There has been a greater than 333 per cent increase in mortality from Merkel cell carcinoma.